The history of materialism and criticism of its present importance / by Frederick Albert Lange ; authorized translation by Ernest Chester Thomas. - Lange, Friedrich Albert, 1828-1875. (Tufts University. Tisch Library., 2016)
1 online resource (3 volumes).; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Series: English and foreign philosophical library.